Serial entrepreneurs in the Waterloo ecosystem - Prescott C. Ensign; Steve Farlow (Journal of Innovation and Entrepreneurship, 2016)
The framework for this study is based on the research and literature related to serial entrepreneurs and entrepreneurial ecosystems. Our sample is 12 serial entrepreneurs within a single context-the Waterloo Region-that has been ranked as one of the top start-up ecosystems in the world. In 2012, it was ranked 16th with 32 % of the start-ups identified as being led by serial entrepreneurs. The study provides an understanding of the characteristics that define a mature ecosystem, with specific input on the Regional Municipality of Waterloo, Ontario, Canada. We profile the 12 entrepreneurs to provide a review of their businesses, the contributions they have made within their ecosystem, and their statements on what they have learned in the process of leading multiple ventures. This research may be useful for communities and nations that seek to focus on entrepreneurship as a means for economic growth. It should also stimulate further research on contextual issues and examine serial entrepreneurs within their own ecosystem.
Keywords: 650; Serial entrepreneurs; Entrepreneurial ecosystem; Venture creation; Waterloo Region